Disease Control Management Strategy in Bali Cattle - Miftahol Horri; Suyanto; R. Ayu Erni Jusnita (Global Writing Academica Researching and Publishing, 2023)
Livestock health is a very important factor in beef cattle farming. Huge losses are often caused by the onset of an attacking disease. Therefore, it is necessary to prevent and control the disease. This study aims to evaluate disease control management strategies in cattle in Indonesia. The method used is a qualitative descriptive research with a literature review method. The results showed that cattle breeders who implemented good disease control management strategies tended to have better livestock health and higher productivity. This study also identified several important factors in the success of Peyang disease control management strategies including disease prevention, treatment, surveillance, quarantine, access restrictions and education. The implication of this study is that cattle farmers must improve their knowledge and skills in disease control management to improve the health and productivity of their livestock.